Coronary heart disease is associated with a worse clinical outcome of hand osteoarthritis: a cross-sectional and longitudinal study. Issue 1 (15th February 2017) - Courties, Alice; Sellam, Jérémie; Maheu, Emmanuel; Cadet, Christian; Barthe, Yoann; Carrat, Fabrice; Berenbaum, Francis
Abstract : Objective: To determine whether cardiometabolic factors are associated with hand osteoarthritis (HOA) symptoms, radiographic severity and progression in a post hoc analysis of the phase III Strontium ranelate Efficacy in Knee OsteoarthrItis triAl (SEKOIA) trial, designed to determine the effect of strontium ranelate on knee osteoarthritis (OA). Methods: Among the 1683 patients randomised in the SEKOIA study, 869 with radiographic HOA at baseline (rHOA≥2 joints with Kellgren-Lawrence grade ≥2) were included in a cross-sectional analysis. For longitudinal study, we included only the 307 patients with rHOA at baseline from the placebo group. We evaluated whether baseline symptomatic HOA, radiographic severity and clinical and rHOA progression were associated with coronary heart disease and/or metabolic diseases (obesity, diabetes and hypertension, dyslipidaemia) by multivariate regression analysis. Results: At baseline, 869 patients (72% women) were included in the cross-sectional analysis; 26% were symptomatic. On multivariate analysis, symptomatic HOA was associated with coronary heart disease (OR 3.59, 95% CI (1.78 to 7.26)) but not metabolic diseases. After a mean follow-up of 2.6 years, for the 307 participants in the placebo group, on multivariate analysis, worse clinical HOA outcome was associated with coronary heart disease (OR 2.91, 95% CI (1.02 to 8.26)). The slow radiographic progression did not allow for revealing any associated factors. Conclusions: Symptomatic HOA and worse HOA clinical course are associated with coronary heart disease. These results strengthen the systemic component of HOA and the association between OA pain and cardiac events. Trial registration number: ISRCTN41323372.